Trash, teaching and the city: the "Big Hole Counter Narrative" project and the "Urban Anthropology: Research Methods and Fieldwork" course at Sol Plaatje University. Issue 1 (2nd January 2018) - Truyts, Carina
Abstract : This essay reflects on an anthropology course developed at one of the two "post-apartheid" universities in South Africa. The course included collaborating with artists and a local dance/ performance troupe. It culminated in a film by Francois Knoetze (featuring collaborators), a musical performance by the Amandla Danca Teatro, and an exhibition by students. Knitting together practice, theory and alternative research and narrative methods, the course intervened on a developmentalist trajectory in the romantic "sparkling" narrative of Kimberley as the "city of diamonds." Alternative, ordinary and sometimes contested stories emerged.